A novel high-frequency indicator of financial integration for monitoring the impact of COVID-19 - Stefano Borgioli; Urszula Kochanska; Francesco Paolo Mongelli; Alessandro Zito (European Central Bank (ECB), 2023)
In early 2020, the rapid spread of the coronavirus (COVID-19) quickly developed into a pandemic. This was followed by a sharp global economic downturn that was extraordinary in its speed, reach and scale. Within days of the first reported COVID-19 cases, the ECB daily Composite Indicator of Systemic Stress soared, and stress in several financial market segments began to flare up. These rapidly emerging financial strains could not be captured by a composite indicator of financial integration at the time because such indicators were low-frequency - principally monthly or even quarterly. The first aim of this paper is to present the steps taken in constructing a novel high-frequency price-based indicator of financial integration (HF-PIFI). Throughout the COVID-19 crisis, this novel indicator was responsive to public health data releases, incoming economic and financial data, and policy announcements. In this sense, it acted as a "thermometer". The second aim of the paper is to use the novel indicator to identify events that were either supportive or damaging with respect to financial integration. This helps to distinguish between the main phases of the pandemic. The third aim of the paper is to review how the novel HF-PIFI indicator performed against the low-frequency indicators of financial integration. Looking back, the signals from the F-PIFI index were quite accurate: the benefits of daily signals based on market data outweigh those of relying on a more limited set of low-frequency data.
Keywords: C82; C83; E58; G10; 330; COVID-19; pandemic; systemic risks; financial integration; new statistical indicators; event studies